Risk-benefit in food safety and nutrition - outcome of the 2019 Parma Summer School - Verhagen, H. (2022)
Risk-benefit assessment is the comparison of the risk of a situation to its related benefits, i.e. a comparison of scenarios estimating the overall health impact. The risk–benefit analysis paradigm mirrors the classical risk analysis one: risk–benefit assessment goes hand-in-hand with risk–benefit management and risk–benefit communication. The various health effects associated with food consumption, together with the increasing demand for advice on healthy and safe diets, have led to the development of different research disciplines in food safety and nutrition. In this sense, there is a clear need for a holistic approach, including and comparing all of the relevant health risks and benefits. The risk–benefit assessment of foods is a valuable approach to estimate the overall impact of food on health. It aims to assess together the negative and positive health effects associated with food intake by integrating chemical and microbiological risk assessment with risk and benefit assessment in food safety and nutrition. The 2019 Parma Summer School on risk–benefit in food safety and nutrition had the objective was to provide an opportunity to learn from experts in the field of risk–benefit approach in food safety and nutrition, including theory, case studies, and communication of risk–benefit assessments plus identify challenges for the future. It was evident that whereas tools and approaches have been developed, more and more case studies have been performed which can form an inherent validation of the risk–benefit approach. Executed risk–benefit assessment case studies apply the steps and characteristics developed: a problem formulation (with at least 2 scenarios), a tiered approach until a decision can be made, one common currency to describe both beneficial and adverse effects (DALYs in most instances). It was concluded that risk–benefit assessment in food safety and nutrition is gaining more and more momentum, while also many challenges remain for the future. Risk-benefit is on the verge of really enrolling into the risk assessment and risk analysis paradigm. The interaction between risk–benefit assessors and risk–benefit managers is pivotal in this, as is the interaction with risk–benefit communicators.